Moroccan Cinema from Below: Re-Visiting Mohamed Osfour’s Film Practice - El Bouayadi Mohamed (Université Mohamed V - AGDAL, Faculté des Lettres et des Sciences Humaines , Rabat, 2020)
This dissertation engages thematically with Mohamed Osfour’s cinematic experience. The aim here is to demonstrate the significance of such an experience and its contribution to the development of Moroccan cinema. This contribution is apparent in Osfour’s clear endeavour to produce a form of cinema that is socially and culturally rooted in Moroccan cultural identity. The main argument of this dissertation is that Osfour’s film practice is worth investigating and his filmography is criticizable. This dissertation asks the following research questions: How has Osfour’s cinematic experience been critically received by conventional film scholarship? Does Osfour’s cinematic experience abide by any stylistic categorization? What types of aesthetics did Osfour try in his cinematic endeavour? Does Osfour’s cinematic experience have any intellectual relevance to the development of Moroccan cinema? Are Osfour’s films criticizable and do they lend themselves to critical scrutiny? Despite its historical primacy and contribution to the development of Moroccan cinema, Osfour’s film practice has received little notice and has been overlooked by conventional film scholarship. Because it was an informal form of cinema practice, Osfour’s experience has been beyond the scope of the critical discourse on film. Conversely, it has been treated as a minor form of cinema, and therefore considered as artistically poor and lacking in artistic merit. Osfour’s films have not been critically approached because they have not been considered worthy of critique. The present study is theoretically approached from the perspective of Cultural Studies and Film Theory. Driven by the desire to re-think and re-visit Osfour’s film practice, this dissertation has found Cultural Studies and Film Theory as the most relevant theoretical frameworks to be deployed in such an endeavour. In terms of its stylistic categorization, Osfour’s filmography will be identified according to three broad concepts: “A cinema of attractions,” “a cinema of narrative integration,” and “a cinema of narrative attractions.” The two first concepts are borrowed from Tom Gunning (1986) in his endeavour to re-visit the legacy of early cinema, whereas the third concept is my own proposal. Gunning’s theoretical framework has been appropriate because of the affinities and similarities between Osfour’s film practice and early cinema. Categorizing Osfour’s filmography stylistically has been useful in the process of its critical investigation. Seen through the prism of early cinema, Osfour’s filmography becomes approachable and criticizable.
Keywords: Moroccan Cinema; Re-Visiting Mohamed Osfour’s Film